PENGARUH OPINION SHOPPING, REPUTASI KAP, AUDIT TENURE, DAN KONDISI KEUANGAN TERHADAP PEMBERIAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR - Ribkha Laura (2020)
This research is a quantitative study aimed to examine the effect of opinion shopping is measured by changing auditors after getting going concern audit opinion, KAP reputation is measured from the KAP big four and KAP non-big four, audit tenure is measured by the length of the engagement period between client and auditors, and financial conditions is measured by the Altman Zscore Modified method of providing going-concern audit opinions. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange and the websites of each company for the 2016-2018 period that were selected using the purposive sampling method. Hypothesis testing in this study using Logistic Regression Analysis with the SPSS program and a significance level of 5%. The independent variable influencing the dependent variable in thus study was shown at 69,8% while the remaining 30,2% was influenced by other factors. The results of thus study explain that opinion shopping, audit tenure and financial conditions have a significant positive effect ongoing concern audit opinion, meanwhile KAP reputation has no effect ongoing concern audit opinion